From Intention to Economic Purchase Decision : The Contribution of Electronic Word of Mouth and Social Media Marketing - Saputra, Dimas Friatna; Syahputra, Erwin (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to determine the influence of the relationship between Electronic Word of Mouth (e-WOM) and Social Media Marketing on purchase intention at Rocket Chicken, Ngronggo Branch, Kediri City. The method used in this study is quantitative, using the accidental sampling technique with a total of 90 respondents. The data collected is primary data, obtained through the distribution of questionnaires. The study found that Electronic Word of Mouth (e-WOM) has a significant effect on Purchase Intention. Purchase Intention influences Purchase Decision, while Social Media Marketing significantly affects both Purchase Intention and Purchase Decision. Purchase Intention does not mediate the effect of e-WOM on Purchase Decision, but it does mediate the effect of Social Media Marketing on Purchase Decision. This study is original in the context of a specific research object, namely Rocket Chicken consumers at the Ngronggo Branch, Kediri City. It also combines e-WOM and Social Media Marketing variables with Purchase Intention as a mediating variable in the decision-making process. The results of this study provide strategic input for culinary business actors, especially Rocket Chicken, to focus more on effective social media marketing strategies in increasing purchase intention and purchase decisions of consumers.